The Influence of Layer Thickness and Deposition Conditions on Structural State of NbN/Cu Multilayer Coatings - Sobol, O. V.; Andreev, A. A.; Meylekhov, A. A.; Postelnyk, A. A.; Stolbovoy, V. A.; Ryshchenko, I. M.; Sagaidashnikov, Yu. Ye.; Kraievska, Zh. V. (Sumy State University, 2019)
The influence of the main physical and technological factors of structural engineering (layer thickness, nitrogen atmosphere pressure and bias potential) on the structural-phase state of the NbN/Cu coatings was studied. It was established that with an increase in the thickness of niobium nitride layers from 8 to 40 nm (in the NbN/Cu multilayer composition), the phase composition changes from the metastable NbN (cubic crystal lattice, NaCl structural type) to the equilibrium ε-NbN phase with a hexagonal crystal lattice. At low pressure PN = 7·10 – 4 Torr in thin layers (about 8 nm thick), regardless of the Ub, the NbN phase is formed. The reason for the stabilization of this phase can be the uniformity of the metallic fcc crystal lattice of the δ-NbN phase with the Cu crystal lattice. As the pressure increases from РN = 7·10 – 4 Torr to 3·10 – 3 Torr, a more equilibrium ε-NbN phase with a hexagonal crystal lattice is formed. An increase in the bias potential during deposition from – 50 V to – 200 V mainly affects the change in the preferred orientation of crystallite growth. In thin layers of the NbN phase (about 8 nm), a crystallite texture with the [100] axis is formed. In layers with a thickness of 40-120 nm, crystallites of the NbN phase are predominantly formed with a hexagonal (004) plane parallel to the growth plane. At the greatest layer thickness (more than 250 nm), the NbN phase crystallites are predominantly formed with a (110) hexagonal lattice plane parallel to the growth plane. The results obtained show great potential for structural engineering in niobium nitride when it is used as a constituent layer of the NbN/Cu multilayer periodic system.

Досліджено вплив основних фізичних та технологічних факторів структурного проектування (товщина шару, тиск атмосфери та потенціал відхилення) на структурно-фазовий стан оболонок NbN/Cu. Встановлено, що при збільшенні товщини шарів нітриду ніобію від 8 до 40 нм (в багатошаровій композиції NbN/Cu) відбувається зміна фазового складу від метастабільного NbN (кубічна кристалічна решітка, структурний тип NaCl) до рівноважної NbN фази з гексагональної кристалічною решіткою. При низькому тиску РN = 7·10 – 4 Торр в тонких шарах (товщиною близько 8 нм) незалежно від Ub відбувається формування NbN фази. Причиною стабілізації цієї фази може бути однотипність металевої ГЦК кристалічної решітки NbN фази з кристалічною решіткою Сu. При збільшенні тиску від РN = 7·10 – 4 Торр до 3·10 – 3 Торр відбувається утворення більш рівноважної NbN фази з гексагональної кристалічною решіткою. Збільшення потенціалу зміщення при осадженні від – 50 В до – 200 В в основному впливає на зміну переважної орієнтації зростання кристалітів. В тонких шарах NbN фази (близько 8 нм) формується текстура кристалітів з віссю [100]. У шарах товщиною 40-120 нм переважно формуються кристаліти NbN фази з площиною гексагональної решітки (004) паралельною площині зростання. При найбільшій товщині шарів (більше 250 нм) відбувається переважне формування кристалітів NbN фази з площиною гексагональної решітки (110) паралельною площині зростання. Отримані результати показують великі можливості структурної інженерії в нітриді ніобію при його використанні в якості складового шару багатошарової періодичної системи NbN/Cu.
Вплив товщини шарів і умов осадження на структурний стан NbN/Cu багатошарових покриттів
Keywords: vacuum arc; period; bias potential; phase composition; structure; solid solution; вакуумна дуга; хімічні реакції; тверді розчини; потенціал зміщення; кристаліти